LEARNINGS AND CHALLENGES TO BRAZILIAN EXPERIENCES IN AGROECOLOGICAL TRANSITION: A SYSTEMATIC REVIEW OF THE LITERATURE (Interdisciplinary Studies Journal, 2024)
The technical-scientific literature records two styles of agriculture, family-based and industrial. However, the industrial agriculture model is predominant in society and is strongly associated with the neoliberal economic school of thought whose reference is exogenous development, the concentration of capital and productive means such as green revolution technologies and the practice of intensive monoculture. The consequences of this hegemonic model include the worsening of social inequality in the countryside, the growth of food insecurity and risks to the environment and climate. The agroecological transition is a gradual movement carried out by family farmers in conjunction with the socio-technical networks present in communities to oppose and stop industrial agriculture. However, the agroecological transition is a complex task. Hence the question: how are the challenges faced in Brazilian experiences on agroecological transition resolved/overcome to promote agroecology? Thus, the objective of the article was to carry out a systematic review of the literature to map the challenges and how they have been resolved or overcome by family farmers. The results indicate that obstacles/blockages in organic production and in the construction of food markets are being overcome by improving multifunctional capacity in family farming.
Keywords: Agroecological transition; Family farming; Systematic Literature Review